A Theory-Based Longitudinal Investigation Examining Predictors of Self-Harm in Adolescents With and Without Bereavement Experiences - del Carpio, Laura; Rasmussen, Susan; Paul, Sally (Frontiers in Psychology, 2020)
Background Research has demonstrated that exposure to suicide can lead to increased vulnerability for self-harm or suicide. As a result, ideation to action models of suicide (e.g., the Integrated Motivational-Volitional Model of Suicide; IMV) recognise exposure as a significant risk factor which may be implicated in the translation of thoughts into actions. However, few studies have tested this theoretical link explicitly within an adolescent population, and examined how it compares to other types of bereavements. Methods A 6-month prospective questionnaire study was conducted with 185 Scottish adolescents aged 11-17 (113 adolescents also completed the questionnaire at follow-up). The questionnaire included measures on experiences with bereavement and lifetime engagement in self-harm, as well as measures of defeat, entrapment, social support, coping, and other psychological variables. Results At baseline, 12% of young people reported exposure to a suicide death, and 61% to a non-suicide death. In addition, 21% of pupils reported ever engaging in self-harm, while 23% had experienced self-harm ideation without engaging in it. Cross-sectional multivariate logistic regressions showed that family social support, glorifying/normalising beliefs about suicide, and family self-harm were significantly associated with self-harm group membership (control, ideation, or enactment groups). At follow-up, 10% of pupils reported exposure to a suicide death and 16% to a non-suicide death for the first time. A total of 26% of the sample reported self-harm at T2 (11% of participants for the first time), and 24% reported self-harm ideation without engaging in it. Multivariate analyses found that self-harm ideation and family self-harm at baseline were the only variables to predict self-harm group membership prospectively, in the expected directions. Bereavement experiences, whether by suicide or non-suicide, did not predict self-harm group status at baseline nor at follow-up. Conclusions This study provides support for the validity of a theoretical model of suicide, even though predictive ability over the 6-months period was limited. Although difficulties with recruitment may have limited the statistical power, this study provides insight into the prevalence and experiences of suicide bereavement among adolescents and the factors related to the onset and maintenance of self-harm.